Capitalizing on opportunities provided by pasture sudden death to enhance livestock sustainable management in Brazilian Amazonia - Eri, Marta; Silva Junior, Carlos Antonio da; Lima, Mendelson; La Scala Júnior, Newton [UNESP]; Oliveira-Júnior, José Francisco de; Teodoro, Paulo Eduardo; Capristo-Silva, Guilherme Fernando; Caione, Gustavo; Peres, Carlos A. (Elsevier, 2020)
Brazil has the largest commercial beef cattle stock on Earth, and most of the cattle produced in the country is bred and finished on pastures. The cattle ranching sector represents a significant source of the country's greenhouse gas (GHG) emissions. Agricultural intensification has been highlighted as one of the main strategies in reaching global food security and reducing deforestation. The Sudden Death Disease (SDD) of pastures, which affects the most planted cultivar of Urochloa brizantha, is degrading pastures in the Amazon, contributing to low production yields and high emission rates. This paper discusses the intensification of pasture production systems and SDD, to examine the potential for pasture renovation to address livestock productivity and GHG balance, emissions and potential sinks. Does SDD represent a blessing or a curse to climate change mitigation in the Brazilian Amazon? A collection of pasture samples were assessed to measure wet and dry weight in areas with and without SDD, which were related to remote sensing data to provide an overall estimate of the total area affected by the SDD in Alta Floresta, a municipal county of southern Brazilian Amazonia. We found that 77.1% of all pastures had been committed to the syndrome, which has forced farmers to renew their pastures. This also has great potential in increasing soil carbon stocks, effectively reducing the CO2 footprint of meat production in those areas. Therefore, we firmly believe that SDD management has provided an opportunity to rebalance the emissions/sequestration equation associated with meat production by the cattle ranching sector in this Amazonin frontier.
Keywords: GHG emission; Land sparing; Land use change; Pasture intensification; Urochloa spp